Empathy as a driver of social entrepreneurship: insights from the Bulgarian context - Ana Todorova; Irina Kostadinova; Nataliya Venelinova (Entrepreneurship and Sustainability Issues)
Social entrepreneurship, understudied as a business and social phenomenon, hides its potential, and what drives those involved in a social activity still needs to be clarified. The paper's authors assume that empathy is the basis of starting a socially significant business and seek confirmation of this thesis in direct communication with social entrepreneurs from Bulgaria. The research methodology is based on the author's conceptual framework, which includes two groups of results – quantitative and qualitative – that aim to confirm or reject the formulated hypotheses. The results show a positive relationship between empathy and starting a socially engaged business. The analysis identifies empathy as a vital catalyst for the social entrepreneur, along with communication skills, emotional intelligence, and critical thinking. The research shows that empathy is a prerequisite for starting a socially engaged business and can significantly contribute to the organisation's success. At the same time, there is a subjective conclusion that Bulgarian social entrepreneurs are not responsive enough, which may hinder social changes and the development of social enterprises in the country. Future research will explore that topic.